Nasal oncocytoma causing unilateral epiphora in an elderly patient: the vital role of nasendoscopy. (9th March 2018) - Murphy, Declan C; Alfiky, Mohamed; Prinsley, Peter
Abstract : Oncocytomas are rare glandular tumours, typically found in salivary glands and kidneys. A 76-year-old man presented to an ophthalmology department after 3 months of persistent right-sided epiphora. Lacrimal syringing and a fluorescein dye test demonstrated an obstruction at the level of the nasolacrimal duct (NLD). Owing to the patient's history of dacryocystitis, endoscopic dacryocystorhinostomy was organised. When in theatre however, nasendoscopy identified a polypoid mass at the lateral aspect of the inferior turbinate, obstructing the right NLD opening. Histopathology confirmed an oncocytoma. There was no local destruction or distant metastases. The mass was resected, a Monoka stent inserted and symptomatic relief achieved. In this case, the cause of epiphora was initially missed because no direct nasal examination was performed. It is vital that patients with unilateral epiphora undergo an endoscopic nasal examination before arranging treatment. This could prevent delayed diagnoses, ensure prompt and appropriate management, and reduce morbidity and mortality.